Composición por tallas y ciclo reproductivo de Pseudupeneus grandisquamis(Pisces: Mullidae) en el Pacífico central Mexicano - Lucano-Ramírez, G. (2006)
From June 1995 to December 1998 we used shrimp trawl nets to capture 492 Pseudupeneus grandisquamis in soft-bottom grounds off the central Mexican Pacific (Jalisco and Colima). The ength-weight ratio indicates allometric growth (p = 0.0035L3.46 y r2=0.97). The total sex ratio was 1:1.15 (females:males). Mean total length was 153.8 mm (range 77-236 mm). A progression in length was found: the highest means were observed at the end of 1996 and during 1997. The mean length of females (162 mm) was longer than in males (150 mm). Four gonadic maturity stages were observed in both sexes; in females the most frequently stage was stage IV (mature gonads, 48.6%), while in males it was stage III (gonads in maturation, 45.0 %). Seven microscopic oocyte development stages were identified. Oocyte development seems to be asynchronous. The mature testicle showed sperm inside the lobular lumen and in the duct. The highest values of the gonadosomatic index, as well as the largest percentages of individuals with mature gonads (at macroscopic and microscopic levels), were observed during winter and summer, suggesting that this species has two reproduction peaks by year. The length at which 50% of the individuals show gonads in maturation (L50) was 183 mm for the females and 181 mm for the males.